Ethnicity and earnings in a mixed race labor market - Ñopo, Hugo; Saavedra, Jaime; Torero, Maximo (University of Chicago Press, 2007)
This study examines the relationship between earnings and racial differences in a context in which various races have coexisted and mixed during several centuries, as is in many parts of the post-colonial world, and specifically Urban Peru. Coarse indicators of racial differences do not suffice in capturing this relationship therefore we introduce a score-based procedure of white and indigenous racial intensities that allows us to approximate these mixed racial heritage. We introduce a score-based procedure of white and indigenous racial intensities that allows us to approximate the heterogeneity within the mestizo population. We construct two types of indicators of racial intensities using a score-based procedure: a single-dimensional indicator of degrees of whiteness; and a two-dimensional indicator combining degrees of both whiteness and indigeneity. This second indicator allows us to study non-linearities in earning differences across mixed white and indigenous racial characteristics. Our estimates from a semi-parametric model show evidence of a race premium for whiteness on earnings, statistically significant among wage earners but not among the self-employed. These results may be consistent with a story of employer discrimination.